Electron hybridization and anharmonic thermal vibration effect on structure transition of SrTiO3 at high-pressure and low-temperature. (January 2017) - Yamanaka, Takamitsu; Ahart, Muhtar; Mao, Ho-kwang; Suzuki, Takeyuki
Abstract: We execute electron density analysis of SrTiO3 at low temperatures up 80 K and high pressures up to 11.88 GPa using X-ray single-crystal diffraction and ab initio quantum chemical molecular orbital (MO) calculation. By changing pressures, the cubic SrTiO3 with perovskite structure goes through a antiferroelastic distortion to tetragonal symmetry above the critical pressure P c =7 GPa with c/a <1 and decreasing with increasing pressure. On the other hand, by changing temperatures, the tetragonal distortion occurs below the critical temperature Tc =105 K with c/a >1 and increasing with lowering temperature. Difference Fourier (D-F) synthesis experimentally proves the residual electron densities Δ ρ ( xyz ) are associated with two different effects: electron hybridization bonding electron and anharmonic thermal vibration atoms. The d–p – π hybridization between Ti(3 d ) and O(2 p ) orbitals is confirmed in the residual electron density, which is deformed from the ideal spherical density conducted by the atomic scattering factor fi using Hartree–Fock (HF) approximation. MO calculation also reveals the electron hybridization. Anharmonic thermal vibration of atoms yields a large effect to the structure transition. Mulliken charges analysis of MO calculation indicates much smaller charges than their formal ionic charges. Their ionicity increases from cubic to tetragonal above Pc and below Tc .